Closed Reduction and Percutaneous Pinning of Pediatric Supracondylar Humeral Fractures. Issue 2 (April 2018) - Vuillermin, Carley; May, Collin; Kasser, James
Abstract : Supracondylar humeral fractures are the most common elbow fractures in children requiring operative intervention. They are classified according to the Gartland system as nondisplaced (type I), displaced with hinging and the posterior cortex intact (type II), and completely displaced (type III). The standard treatment for type-II and III fractures is closed reduction and percutaneous pinning. The timing of surgery depends on the severity of the fracture and the presence of any neurovascular injury. Preoperative assessment of the neurologic and vascular status is imperative, and can be challenging in a young child. The steps of the surgical procedure consist of the following. Position the patient supine with the affected extremity on a fluoroscopy detector or hand-table. Perform closed reduction. Apply longitudinal traction with the elbow in 30° of flexion. Correct medial or lateral translational displacement. Correct varus or valgus malalignment. Maintain traction and flex the elbow, placing pressure over the olecranon process to correct extension at the fracture site. Assess reduction using anteroposterior, oblique, and lateral fluoroscopic views. Place divergent pins from the lateral side, using 2 pins for type-II and 3 pins for type-III fractures. Assess stability by moving the elbow through a range of motion under live fluoroscopy in the lateral projection. If the fracture is determined to be unstable with lateral-only pins, proceed with medial pin placement through a mini-open approach. Cut the pins and bend them outside the skin. Then apply a long-arm bivalved cast. The pins are removed between 3 and 4 weeks postoperatively, depending on patient age, and range of motion is initiated. Elbow stiffness is common for 4 to 6 weeks, but a return to a nearly full range of motion can be expected. Resumption of normal activities should be delayed until the fracture is fully healed and the range of motion is nearly normal.